The influence of top management team diversity and networking towards firm innovativeness in achieving sustainable firm performance - Sri Sarah Maznah, Mohd Salleh (2017)
The main objective of this study is to evaluate the relative influence of Top Management Team (TMT) diversity and networking on firm innovativeness, and their overall effect on sustainable firm performance, among Permodalan Nasional Berhad (PNB) invested companies in Malaysia. Moreover, it examined the mediating effect of firm innovativeness towards relationships of TMT diversity and networking with firm performance, and assessing the moderating effect of innovation types on the relationship between firm innovativeness and firm performance. The motivation of this study was driven by the inconclusiveness of previous research findings on the influence of TMT characteristics towards firm innovativeness. Furthermore, there were limited studies which examined the influence of firm innovativeness on sustainable firm performance, though the importance of innovation for long-term sustainability had been recognized by the Malaysian government. Data were collected through survey questionnaires which were randomly distributed to a sample of 96 PNB invested companies, with 47% response rate. They were analysed by employing PLS-SEM technique. Results obtained indicated that TMT diversity, TMT networking and firm innovativeness significantly enhanced sustainable firm performance, demonstrating the essential aspects to be considered by practitioners. Additionally, the mediating role of firm innovativeness between TMT networking and firm performance was established. Results also showed that process and organizational innovation moderated the relationship between firm innovativeness and firm performance. Novelty of this research was pioneering the overall impact of TMT diversity and networking, the mediating role of firm innovativeness, and the moderating effect of innovation types which explained 81% of variance in sustainable firm performance. Hence, attained results provided further explanations to the current literature and empirically extended the Upper Echelon Theory to include TMT diversity, TMT networking, mediating role of firm innovativeness, and moderating effects of innovation types towards sustainable firm performance. Finally, the research offers recommendations to management researchers, policymakers and PNB.